ViAggre: Making Routers Last Longer! - Ballani, Hitesh, Paul Francis; Cao, Tuan; Wang, Jia (Proc. of workshop on Hot Topics in Networks (HotNets-VII), 2008)
This paper presents ViAggre (Virtual Aggregation), a “configuration-only” approach to shrinking the routing table on routers. ViAggre applies to legacy routers and can be adopted independently and autonomously by any ISP. ViAggre is effectively a scalability technique that allows an ISP to modify its internal routing such that individual routers in the ISP’s network only maintain a part of the global routing table. We find that ViAggre can shrink the routing table on routers by more than an order of magnitude while imposing negligible traffic stretch.